2015
DOI: 10.1164/rccm.201408-1562oc
|View full text |Cite
|
Sign up to set email alerts
|

Increased Resource Use in Lung Transplant Admissions in the Lung Allocation Score Era

Abstract: Rationale: In 2005, the lung allocation score (LAS) was implemented to prioritize organ allocation to minimize waiting-list mortality and maximize 1-year survival. It resulted in transplantation of older and sicker patients without changing 1-year survival. Its effect on resource use is unknown.Objectives: To determine changes in resource use over time in lung transplant admissions.Methods: Solid organ transplant recipients were identified within the Nationwide Inpatient Sample (NIS) data from 2000 to 2011. Jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 30 publications
0
58
0
Order By: Relevance
“…We have previously demonstrated increased transplant admission resource use within the post-LAS era (2). This study builds on that work by describing recipient factors associated with increased resource use.…”
Section: Original Researchmentioning
confidence: 79%
See 2 more Smart Citations
“…We have previously demonstrated increased transplant admission resource use within the post-LAS era (2). This study builds on that work by describing recipient factors associated with increased resource use.…”
Section: Original Researchmentioning
confidence: 79%
“…In the present era of increased emphasis on health-care cost containment and in light of the recent recognition of increasing resource use in lung transplantation, there is a need to identify how to reduce lung transplant cost without sacrificing lung transplant access, quality, or outcomes (2). In this study, we have shown that low-volume transplant centers provide transplant admission care at a greater cost than high-volume centers while also demonstrating higher adjusted in-hospital mortality and excess risk for early hospital readmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(6) Morbidity and mortality after the first post-operative year have also increased in this period. (7, 8)…”
Section: Introductionmentioning
confidence: 99%
“…After lung transplants, nearly the same proportion of patients die within the first postoperative year (2). Notably, serious morbidity after transplant is increasing, with resultant disability and associated decrements in health-related quality of life (3,4). Although known risk factors for death are already incorporated into lung allocation in the United States (Lung Allocation Score [LAS]), persistently high mortality and increasing morbidity underscore the need to identify novel risk factors for poor outcomes to maximize the individual and societal benefit of lung transplants (5).…”
mentioning
confidence: 99%